2018
DOI: 10.23917/humaniora.v19i2.6809
|View full text |Cite
|
Sign up to set email alerts
|

Efl Teacher’s Belief and Practice on Integrating Ict in the Classroom: A Case Study on the Implementation of Samr Model in Teaching Reading Descriptive Text at Ma Assalam, Sukoharjo

Abstract: 21st century learning demands the integration of Information and CommunicationTechnology (ICT) in teaching and learning process. Regarding this issue, this research isaimed at investigating English as a foreign language (EFL) teacher’s belief and practices onthe integration of ICT in English language teaching. To reach the objective, a case study onan individual teacher was used in this research. The participant was purposively andtheoretically selected because she was considered as the informant who could giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…This means that teachers need to be involved in training programs to be able to use GCA effectively. This is consistent with previous studies [24], [30] which emphasized the importance of teachers' technology training to integrate technology in the classroom. Chamorro and Rey [29] stated that there is a difference between teachers' belief and the implementation of technology in terms of matching the teaching practice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This means that teachers need to be involved in training programs to be able to use GCA effectively. This is consistent with previous studies [24], [30] which emphasized the importance of teachers' technology training to integrate technology in the classroom. Chamorro and Rey [29] stated that there is a difference between teachers' belief and the implementation of technology in terms of matching the teaching practice.…”
Section: Discussionsupporting
confidence: 93%
“…and Ulfa [30] suggested that before using ICT, teachers should be knowledgeable with ICT by receiving training on how to use it. Furthermore, regarding the benefits of this application for the EFL students, the findings reveal that GCA has some advantages and disadvantages for them.…”
Section: Discussionmentioning
confidence: 99%
“…It consisted of one page only" Zoom, google classroom, google Forms, WhatsApp, and Kine Master to make a video were the applications utilized by the honorary teachers in teaching or preparing the lesson online. Teachers should care for their students' motivation and participation by demonstrating proper personal and teaching behavior integrated with ICT in the classroom [23]. The same application were also stated in the finding provided by other researchers such as [7-9, 11, 15-17], the honorary teachers argued the same opinion as honorary teacher 1 below: "Formerly, I used Zoom.…”
Section: Resultssupporting
confidence: 52%
“…Once students utilize their cell phones to improve their assignments or study, augmentation is rare. (Budiman et al, 2018) found that teachers in Indonesia frequently fall under the category of substitution and augmentation, which is dominated by modification and redefinition of the level of ICT integration in teaching.…”
Section: Discussionmentioning
confidence: 99%